A catastrophic case of venous air embolism in a patient undergoing posterior fossa surgery - Guleria, Ruby; Sharma, Anita; Raizada, Maninder Singh; Singh, Neetiksha (International Journal of Research in Medical Sciences, 2022)
Posterior cranial fossa surgeries pose increased risk of venous air embolism (VAE) due the associated pressure gradient. Early detection of VAE is of paramount importance to avoid the disastrous consequences. We, hereby report a case of catastrophic VAE in a 47-year-old male undergoing surgery for glioblastoma.